Contraception Use and Counseling at a Student-Run Free Clinic - Amanda Pitre; Yamini Mulla; Bianca Arboleda; Eliza Nguyen; Heather Stewart; Emma Hale; Elizabeth Cook; Alexander Shahin; Lucy Guerra; Deborah Trehy; Karim Hanna; Eduardo Gonzalez (Journal of Student-Run Clinics, 2022)
Background: In the United States, about half of all pregnancies are unplanned. Unplanned pregnancy carries increased risks to patient and fetus and is increased independently by both poverty and being a racial or ethnic minority. The purpose of this study was to examine the percentage and types of contraceptives used by patients at the student-run Building Relationships and Initiatives Dedicated to Gaining Equality (BRIDGE) Healthcare Clinic and determine if clinic staff provided appropriate annual contraceptive counseling.Methods: A retrospective chart review was performed for all active BRIDGE patients that were female and aged 18-60 between 2015 and 2020. Information collected included demographics, obstetric history, tobacco use, medical history of deep vein thrombosis (DVT) or hypertension, and contraception use. Results: Of 145 patients reviewed, 77.2% used contraception at some point during the study period. Surgical contraception was the most common form used. No patients with a documented history of DVT or tobacco use used estrogen-containing contraception during the study period. One patient out of the twenty with documented hypertension used an estrogen-containing form of contraception for one year.Conclusions: Overall, our clinic counseled the majority of patients of child-bearing age on contraception use. Contraception use in our population is above the national average and is appropriately prescribed.